Usability Testing Pada Prototype Antarmuka Aplikasi E-commerce Ez Buy Berbasis Mobile - Krisnayana, Nyoman; Astuti, Luh Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
One of the reasons for developing digital-based application designs is to solve certain problems experienced by users. In its development, several stages and processes are needed that directly involve potential users. Involvement aims to determine the needs and expectations of users in solving a problem. One method to determine the level of user needs is the usability testing method. Usability testing involves testers and participants. The examiner will ask participants to perform a number of tasks. As participants perform a number of tasks, the examiner will observe behavior and listen to feedback during the test. In this case, usability testing is carried out on the design of a mobile-based e-commerce application called Ez Buy. The purpose of usability testing on the Ez Buy application prototype is to find out the extent of user experience and user expectations of the application prototype design. This study aims to determine the participant's behavior towards a feature in the application prototype.